2015
DOI: 10.1111/jce.12849
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age on 5‐Year Outcomes After Atrial Fibrillation Catheter Ablation

Abstract: Age significantly impacts outcomes after AF ablation when analyzed with long-term follow-up. These data highlight the progressive nature of AF and the need to consider interventions early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Finally, age is a significant factor that is associated with disease progression in AF . Bunch et al reported that age was a significant factor in determining outcomes after catheter ablation for AF . Furthermore, Kosiuk et al with the DR‐FLASH score (diabetes mellitus, renal dysfunction, persistent form of AF, left atrial diameter > 45 mm, age > 65 years, female sex, and hypertension) and Letsas et al with the CHA 2 DS 2 ‐VASc score highlighted the importance of age as an independent predictor of arrhythmia recurrence after catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, age is a significant factor that is associated with disease progression in AF . Bunch et al reported that age was a significant factor in determining outcomes after catheter ablation for AF . Furthermore, Kosiuk et al with the DR‐FLASH score (diabetes mellitus, renal dysfunction, persistent form of AF, left atrial diameter > 45 mm, age > 65 years, female sex, and hypertension) and Letsas et al with the CHA 2 DS 2 ‐VASc score highlighted the importance of age as an independent predictor of arrhythmia recurrence after catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of thromboembolism may persist in the elderly population over 75 years of age undergoing AF ablation regardless of whether sinus rhythm is apparently maintained . A number of studies that have specifically focused on reporting the outcomes of AF ablation in older individuals and several randomized trials have included patients who were >75 years of age . The results of these studies provide evidence that catheter ablation of AF has an acceptable safety and efficacy profile in the elderly over the age of 75 or 80 years.…”
Section: Choice Of Rate Vs Rhythm Control In Elderly Af Patientsmentioning
confidence: 99%
“…The results of these studies provide evidence that catheter ablation of AF has an acceptable safety and efficacy profile in the elderly over the age of 75 or 80 years. Age has the significant impact on the long‐term outcomes of AF ablation; for every 10‐year increase in age, there was a higher multivariate‐adjusted risk of AF recurrence, death, and major cardiac events . Furthermore, the complications of the procedure are somewhat increased in older individuals, the need for concomitant antiarrhythmic therapy postablation is greater, and the efficacy is somewhat reduced .…”
Section: Choice Of Rate Vs Rhythm Control In Elderly Af Patientsmentioning
confidence: 99%
“…Several retrospective cohort studies demonstrated that CA was safe and effective in maintaining sinus rhythm for elderly patients and associated with lower mortality and stroke risks. [ 8 9 ] The recent trial (AATAC-AF study) randomized patients with persistent AF and HF to AF ablation or treatment with amiodarone. The results showed that CA was more effective than amiodarone in preventing recurrent AF and was associated with a lower rate of hospitalization and mortality.…”
Section: Ndications and P Atient mentioning
confidence: 99%